2021
DOI: 10.1182/bloodadvances.2020003521
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 defines erythroleukemia metabolism by controlling the lineage-specific transcription factors GATA1 and C/EBPα

Abstract: Acute myeloid leukemia (AML) is a heterogenous malignancy characterized by distinct lineage subtypes and various genetic/epigenetic alterations. As with other neoplasms, AML cells have well-known aerobic glycolysis, but metabolic variations depending on cellular lineages also exist. Lysine-specific demethylase-1 (LSD1) has been reported to be crucial for human leukemogenesis, which is currently one of the emerging therapeutic targets. However, metabolic roles of LSD1 and lineage-dependent factors remain to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The above SERS results further confirmed that metabolisms of these aromatic amino acids could be involved in anaplerosis, and together with glycine in glycine, serine and threonine metabolism for further involvement in arginine and proline metabolism 35,36 . Accumulating data from SERS and NMR suggested genetic abnormality as major determinant of AML prognostic characteristics, and several reports have recently highlighted the role of specific mutations in metabolic features 37,38 . Thus, lineage identity and genetic mutations may cooperatively direct metabolic reprogramming that allows AML to be divided into risk subgroups based on their characteristics of karyotypes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The above SERS results further confirmed that metabolisms of these aromatic amino acids could be involved in anaplerosis, and together with glycine in glycine, serine and threonine metabolism for further involvement in arginine and proline metabolism 35,36 . Accumulating data from SERS and NMR suggested genetic abnormality as major determinant of AML prognostic characteristics, and several reports have recently highlighted the role of specific mutations in metabolic features 37,38 . Thus, lineage identity and genetic mutations may cooperatively direct metabolic reprogramming that allows AML to be divided into risk subgroups based on their characteristics of karyotypes.…”
Section: Discussionsupporting
confidence: 57%
“…35,36 Accumulating data from SERS and NMR suggested genetic abnormality as major determinant of AML prognostic characteristics, and several reports have recently highlighted the role of specific mutations in metabolic features. 37,38 Thus, lineage identity and genetic mutations may cooperatively direct metabolic reprogramming that allows AML to be divided into risk subgroups based on their characteristics of karyotypes. We may propose that AML subjects were typically accompanied by amino acids and nucleotides metabolisms and may progress to very different prognostic outcome with certain molecular events.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in hemoglobin is an intriguing observation and is likely to address the issue of anemia associated with ruxolitinib. A possible explanation for this observation is that the modulation of transcription by LSD1 is lineage-specific or that expression of the γ-globin gene is altered with LSD1 inhibition [86,87]. Eighty-five percent of patients had stable or improved fibrosis score of at least one grade.…”
Section: Clinical Data Of Lsd1 Inhibitors In Myelofibrosismentioning
confidence: 99%
“…In the second step of glucose metabolism, previous studies in leukaemia have described miR-15a and miR-16-1 as targeting the aldolase A (ALDOA), which converts fructose-1,6-bisphosphate to glyceraldehyde 3-phosphate and dihydroxyacetone phosphate in the glycolysis pathway [ 322 ] ( Figure 2 ). Connecting glucose uptake indirectly to activation of epigenetic enzymes with dual activity, in AML, LSD1 stabilises the transcription factor GATA1 on protein level and epigenetically silences the GATA1 negative regulator C/EBPα, thus promoting glucose metabolism [ 323 ]. In haematological malignancies, e.g., AML, MDS, and CML, LSD1 contributes to leukaemogenesis [ 324 ].…”
Section: The Teamwork Between Epigenetics and Metabolism In Haematological Malignanciesmentioning
confidence: 99%